Deictic Dimensions in Translation: Analysis of Personal Deixis in the Indonesian and Arabic Versions of Blue Lock Comics - Muhamad Raihan; Hizbullah, Nur; Abdil Ghany, Sayyed Zuhdi (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
This study explores the use of personal deixis in the Indonesian and Arabic translations of the Japanese manga Blue Lock, emphasizing the impact of linguistic and cultural nuances on translation. Using Alan Cruse's theory of personal deixis, the research examines first-, second-, and third-person categories through a qualitative descriptive approach. Data from official translations by Gramedia (Indonesian) and مانجا العربية للشباب (Arabic) were analysed using purposive sampling, documentation, and content analysis. The findings reveal notable differences: Arabic employs 276 instances of personal deixis with greater diversity due to its gendered and number-specific pronouns, while Indonesian uses 145 instances, reflecting simpler, contextually flexible deixis. Functions such as subject, object, possession, and postposition were more richly contextualized in Arabic. These variations are influenced by linguistic structures, cultural norms, and translators’ interpretive decisions, affecting narrative localization. By examining a genre seldom studied in pragmatics, this research highlights the challenges of translating context-sensitive expressions in popular media and underscores the intricate interplay between language and culture in translation.